Course Review Horay-Based Bamboo Dancing in 21st Century Learning: How Can We Assess Students' Mathematical Creative Thinking? - Suherman, Suherman; Lakatos, Kristóf; Muhammad, Rosida Rakhmawati; Khoiriyah, Binti; Komarudin, Komarudin (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
Education in the 21st-century era can provide students with learning experiences that influence individual growth. This study aimed to determine the effect of integrating the Bamboo Dance learning model and Course Review Horay on students' mathematical creative thinking. The design of this study was quasi-experimental. Data collection instruments were open-ended test questions of mathematical creative thinking. The normality test and the homogeneity test were used as the analysis techniques. The hypothetical testing was performed using one-way ANOVA and Scheffe's method. The results of the analysis showed that the data were normally distributed and homogeneous. As a result of applying the Bamboo Dance learning model integrated with Course Review Horay, the students' mathematical creative thinking was better than the conventional learning model. The Bamboo Dance Model can provide information equally. The Course Review Horay's learning model can make students happy during the learning. This research implies that lecturers can apply BD-CRH as an alternative in improving students' mathematical creative thinking.